Building operational excellence : IT people and process best practices - Allen, Bruce (Bruce R.); Kutnick, Dale. (Hillsboro, OR : Intel Press ; Boston, MA : Addison-Wesley, 2002)
This book shows IT managers exactly how to assess their own organizational processes, and then improve those processes to "best practice" levels. Drawing on META Group's worldwide enterprise consulting experience, it introduces a new way to understand IT processes, and a step-by-step approach to defining goals, filling in gaps, eliminating weaknesses, and achieving excellence.
Includes bibliographical references (p. 206) and index.
oif 28/01/15
Loan
Keywords: Information technology -- Management -- Handbooks, manuals, etc; Information resources management -- Handbooks, manuals, etc; Information technology -- Evaluation -- Handbooks, manuals, etc